Pemanfaatan Drone sebagai Bagian dari Kontra Terorisme: Tinjauan pada Regulasi dan Prosedur Tetap Pengamanan - Muhammad Zaenuddin Firmansyah; Puspitasari Puspitasari (Nakhoda: Jurnal Ilmu Pemerintahan, 2021)
This paper aims to review and evaluate the use of drones in terms of regulations and fixed procedures for safeguarding VVIP and Indonesia's National Vital Objects against drone attacks based on the pathetic incident that befell the President of Venezuela and the National Vital Object of Saudi Arabia. This research uses a qualitative approach with descriptive analysis methods. Data collection techniques are carried out by conducting interviews with related officers, equipped with document studies regarding regulations and carried out so that it is easier to understand the importance of the role of security against VVIP and National Vital Objects combined with potential terrorists using unmanned aircraft (UAV) referring to theories cumulative extremism, rational choice and routine activity. As there are regulations on the use of the latest drones, the Paspampres conducts anti-drone security statically and mobile and the Police are making efforts to safeguard National Vital Objects that keep up with the times. Although drone terrorist attacks have not actually occurred in Indonesia, researchers recommend making regulations in the form of data on drone sellers and buyers by the Ministry of Transportation assisted by the Police, building laboratories and strengthening anti-drone technology in border areas and as a sky monitoring system, forming a coalition of institutional cooperation or related institutions to the anti-drone task force, special forces training, and forming anti drone units such as D'Artagnan.